Determinants of corporate effective tax rates: evidence from the euro area. Issue 3 (27th October 2020) - Barbera, Antonio; Merello, Paloma; Molina, Rafael
Abstract : Purpose: The purpose of this paper is to investigate the effect of the determinants of corporate effective tax rates (ETR) of listed companies in euro area. Design/methodology/approach: With a large and recent panel of 2, 870 listed companies for the period 2005–2016, the authors use the generalized moments method (GMM) to estimate global models for three groups of countries and specific models for six selected countries: Germany, Spain, France, Italy, Belgium and Greece. Findings: The results confirm that ETR have different determinants depending on the countries analyzed. There is a significantly positive relationship with leverage and negative with size and financial profitability. However, economic profitability shows a statistically positive effect in the new members, but negative effect on old ones. In the individual analysis, Germany and Spain maintain this negative association with return on assets (ROA), but Belgium and Greece show a positive effect. The effect of the economic cycle shows statistically relevant, negatively in Germany but positively in Belgium and Greece. Originality/value: This paper makes a novel contribution to the current debate on the need for harmonization of corporate income tax in the European Union (EU). For the first time, the group of countries whose common currency is the euro is considered with a great level of detail. In addition, the impact derived from the enlargement of the euro area and the individual analysis of the main countries is included. The European authorities must take into account the specific differences found in the ETR determinants because it hinders to take measures that limit tax competition. Abstract : Propósito: El propósito de este artículo es investigar el efecto de los determinantes del tipo impositivo efectivo (TIE) del impuesto de sociedades de las empresas que cotizan en la zona del euro. Diseño/metodología/enfoque: Utilizando un panel de 2, 870 compañías cotizadas en el período 2005–2016, los autores utilizan el Método de Momentos Generalizados (GMM) para estimar modelos globales para tres grupos de países y modelos específicos para los seis países seleccionados: Alemania, España, Francia, Italia, Bélgica y Grecia. Resultados: Los resultados confirman que el TIE tiene diferentes determinantes en función de los países analizados. Entre antiguos y nuevos miembros se evidencia una relación significativamente positiva con el apalancamiento y negativa con el tamaño y la rentabilidad financiera. Sin embargo, la rentabilidad económica muestra una relación estadísticamente positiva en los nuevos, pero negativa en los antiguos. En el análisis individual, Alemania y España mantienen esta asociación negativa con el ROA, pero Bélgica y Grecia evidencian un efecto positivo. El efecto del ciclo económico sí resulta estadísticamente relevante, de forma negativa en Alemania, pero positiva en Bélgica y Grecia. Originalidad/valor: Este artículo hace una novedosa contribución al debate actual sobre la necesidad de armonizar del impuesto de sociedades en la Unión Europea. Por primera vez, se considera el grupo de países cuya moneda común es el euro con gran nivel de detalle, así como el impacto de su ampliación y la comparativa individual entre sus principales países. Las autoridades europeas deberían tener en cuenta las específicas diferencias encontradas en los determinantes del ETR, tanto entre antiguos y nuevos miembros como por países, porque dificultan la adopción de medidas de armonización que limiten la competencia fiscal entre países comunes.